2021
DOI: 10.1016/j.jtumed.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 crisis: Influence of eHealth literacy on mental health promotion among Saudi nursing students

Abstract: Objective This study aims to determine the influence of eHealth literacy on mental health promotion among Saudi nursing students. Method This cross-sectional study was conducted from 19 April to 21 May 2020. A total of 468 nursing students responded to the self-administered online survey. Two instruments, namely, the eHealth Literacy Scale and the Positive Mental Health Scale, were used. Statistical tools such as frequency, percentage, mean, and standard deviation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
2
11
1
Order By: Relevance
“…In the studies conducted with nursing students during the pandemic process, it is stated that the average score obtained from the E-SYO scale is high. [ 21 , 22 ] In our study, it was found that the health literacy levels of the students were close to similar studies.…”
Section: Discussionsupporting
confidence: 86%
“…In the studies conducted with nursing students during the pandemic process, it is stated that the average score obtained from the E-SYO scale is high. [ 21 , 22 ] In our study, it was found that the health literacy levels of the students were close to similar studies.…”
Section: Discussionsupporting
confidence: 86%
“…The eHealth literacy research in the Middle East and the Arab world is limited to affluent countries of the Gulf-Cooperating Council (GCC), 56 including Kuwait 57 and Saudi Arabia, 5860 and Jordan. 61 Most of these studies used the eHEALS to assess eHealth literacy among internet users, 57 nursing students, 60,61 and patients living with diabetes 58 and breast cancer, 59 demonstrating the instrument's flexibility and convergent validity. Recently, the eHEALS was validated in Arabic among a sample of native speakers living in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to Murphy et al, the misinformation on social media may frame a person’s knowledge of the efficacy of an intervention [ 31 ]. Thus, students should be taught how to appraise information on social media to prevent misleading concepts [ 32 ], which will affect knowledge and behavior on FM use.…”
Section: Discussionmentioning
confidence: 99%